Standar Ganda di Masyarakat Muslim: Analisis Keadilan Gender dan Ushul Fiqih - Fayza Farahnaz,; Wiwin Handayani,; Muhammad Sendi Hendrawan,; Muhamad Aufa,; Tenny Sudjatmika, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research explores the concept of fairness between genders, using ushl fiqh, which is islamic legal theory, to analyze the phenomenon of double standards in Muslim communities. These double standards are frequently manifested in differential treatment between men and women in various aspects of life, such as inheritance rights, testimony, and social roles, which often contradict the essence of justice taught in the Qur’an and Sunnah. Employing a critical analysis of primary sources of ushl fiqh including qiyas, ijma', and istishab as well as contemporary Islamic feminist perspectives, this research identifies the roots of double standards influenced by patriarchal interpretations and historical cultural contexts. The findings demonstrate that a more inclusive and contextual application of ushl fiqh can serve as a tool for reforming discriminatory social practices, thereby promoting authentic gender justice. The study concludes by emphasizing the importance of reinterpreting fiqh to support gender equality in modern Muslim societies, with implications for educational and legal policy.